DEVELOPING PROFESSIONAL ATTITUDES OF PENAL STAFF - Gavrina, Elena; Kashintseva, Irina; Pozdnyakov, Vyacheslav; Simakova, Tatyana; Kalashnikova, Maria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article presents the results of the empirical research, the study of the influence of individual psychological characteristics of the penal staff on the developing of professional attitudes in the process of training at the FPS training centers. The research distinguishes among three groups of penal employees according to individual psychological characteristics. The article shows statistically significant differences in individual psychological characteristics that affect the developing of professional attitudes in the process of training at the FPS training centers. The research results show that the most efficient professional attitudes are most often developed among employees characterized by the following individual psychological characteristics: stress resistance, threats resistance, resoluteness, ability to control their emotions and behavior, ability to cope with a large amount of work and so on. The article also presents the results of the additional study proving that there are no significant differences in the distinguished groups in terms of such indicators as demographic data, socio-psychological climate, service relationships, needs obtained while fulfilling official duties, degree of the regulatory framework development, management style, etc. The empirical study reveals that such personality traits as negligence, excessive trustfulness, inability to control one’s emotions and impulsive drives can exert negative impact on the performance of official tasks by the penal staff. The research results presented in the article can be used in the educational process at the FPS training centers and in the work of the penitentiary psychologist.